MONSTER MASTER - Pryor, Shawn; Ficorilli, Francesca (North Mankato, Minnesota : Stone Arch Books, an imprint of Capstone, 2022)
Villain Cynthia Cyber has trapped The Gamer's friends in her dangerous Power Combat video game, so if he can not rescue his friends in just ten minutes, they will be stuck in the electronic world forever as monsters.
Ages 8-11. Grades 4-6.
Keywords: Monsters -- Juvenile fiction; Video games -- Juvenile fiction; Heroes -- Juvenile fiction